A study on the elements of graphic design in the success of visual communication / Idrees Abdul Wahab - Abdul Wahab, Idrees (2010)
Visual communication is another method of communication we used everyday. It's not like verbal or written, that we respond back the same way, we don't talk back to pictures, but we respond by telling ourselves to agree with the visual message. Interestingly, most of us don't aware that we communicate to visual message, directly or undirectly. Interacting with it makes visual communication the fastest medium of communication. All these visual that we saw were arranged artistically and objectively to communicate to us. It is done with the help of graphic elements. Line, shape, mass, texture and colour are the 'tools' that are used in structuring the 'visual words'. These tools have unique styles and characters that related to human psychology. Red signify luck or courage, circle defines unity or lines used to guide the eyes. This study will look into how these elements behave in making visual communication a success. Interestingly, responding to visual message means that we are visual literate to the visual message. We are nurturing our visual thinking and creative thinking by interacting with the visuals. The need to learned and know how to use visual communication is important to our survival in the 21" century as this method of communication has prove itself as being the fastest and effective way to influence the people.